Kevin Carson as Dr. Jekyll and Mr. Hyde - Block, Walter E. (2015)
In this essay, the author elaborates a critical analysis of the work Studies in Mutualist Political Economy, by Kevin Carson. The author’s criticism centers around Carson’s adoption of the labor theory of value as the fundamental element of his theoretical framework. Besides, the author exposes several misconceptions that Carson presents regarding many aspects of libertarianism.